Promised Land: Settlement Schemes in Kenya, 1962 to 2016. (August 2021) - Boone, Catherine; Lukalo, Fibian; Joireman, Sandra F.
Abstract: Smallholder settlement schemes have played a prominent role in Kenya's contested history of state-building, land politics, and electoral mobilization. This paper presents the first georeferenced dataset documenting scheme location, boundaries, and attributes of Kenya's 533 official settlement schemes, as well as the first systematic data on scheme creation since 1980. The data show that almost half of all government schemes were created after 1980, as official rural development rationales for state-sponsored settlement gave way to more explicitly welfarist and electoralist objectives. Even so, logics of state territorialization to fix ethnicized, partisan constituencies to state-defined territorial units pervade the history of scheme creation over the entire 1962–2016 period, as theorized in classic political geography works on state territorialization. While these "geopolitics" of regime construction are fueled by patronage politics, they also sustain practices of land allocation that affirm the moral and political legitimacy of grievance-backed claims for land. This fuels on-going contestation around political representation and acute, if socially-fragmented, demands for state-recognition of land rights. Our findings are consistent with recent political geography and interdisciplinary work on rural peoples' demands for state recognition of land rights and access to natural resources. Kenya's history of settlement scheme creation shows that even in the country's core agricultural districts, where the reach of formal state authority is undisputed, the territorial politics of power-consolidation and resource allocation continues to be shaped by social demands and pressures from below. Highlights: New georeferenced data tracks Kenyan settlement schemes since 1962. Data over more than five decades suggests changing purpose of land settlement schemes. State territorialization strategies through land allocation are a constant over time. Land hunger and societal demands for land shape state practices and policies. Current policy debates call for new research on settlement, land allocation, and agriculture in Kenya.